New constitution and media freedom in Libya: journalists’ perspectives - AlAshry, Miral Sabry (Journal of information, communication & ethics in society (Online), 2021)
Purpose The purpose of this study is to investigate Libyan journalists’ perspectives regarding the media laws Articles 37,132, 38 and 46, which address media freedom in the new Libyan Constitution of 2017. Design/methodology/approach Focus group discussions were done with 35 Libyan journalists, 12 of them from the Constitution Committee, while 23 of them reported the update of the constitution in the Libyan Parliament. Findings The results of the study indicated that there were media laws articles that did not conform to the international laws and United Nations treaties, which the Libyan Parliament committee approved. Another finding from the journalists was the Constitution should provide and guarantee press freedom, while media laws articles approved to put a paragraph about “censorship” in the press and media as a tool to silence government opposition. In addition, journalists indicated future constitution should redraft Article 38 to conform with Article 19 of the “International Covenant on Civil and Political Rights,” to support the “principles of freedom of expression and information” without control. Moreover, Article 46 needs to be changed and linked to the “provisions of international law on the right of information access” to improve the access and dissemination of information in the media. Practical implications Redrafting the constitution articles in the future can be summarised as follows: First, the Libyan Constitution should provide and guarantee press freedom without any censorship and include clear articles to protect journalists in conflict zones. Second, Articles 37,132 and 38, about “freedom of information and publication,” need to be redrafted to link with Article 19 of the “International Covenant on Civil and Political Rights,” to support the principles of freedom of expression and information, and the use of this right must not be subject to prior control. Third, Article 46 needs to be changed and linked to the provisions of “International law on the Right of Access to Information” to improve access and dissemination of information in the media to protect confidentiality sources. The most important articles should be implemented (freedom of information and personal information act) because after the Arab Spring revolutions, there was a transitional period in societies and a change in the constitutions of Tunisia and Egypt. They developed legal articles about media freedom so that Libya resembles other Arab countries. From that point, the journalists recommended that all information should be protected from government interference to ensure transparency, combat corruption and protect independent journalists. These articles will open the way to add more development articles to media freedom rules in the Journalists’ Syndicate. Fourth, there are also various types of threats encountered by journalists in their work. In pursuit of their right and freedom of expression, they recommended that Libya must establish an independent self-regulatory media that are free from political and economic influence. Fifth, journalists need licenses for them to work through the syndicate. The new syndicate should play an active role to safeguard the rights of journalists, activists and media entities to carry out their work and end the self-censorship. Sixth, the constitution should also add articles to end the impunity and change the articles in the penal code. Overall, the journalists covering the conflict and war are encountering threats, violence and imprisonment. As a result, Libyan journalists must seek new legislation to defend independent journalism and freedom of expression in their deeply divided country. In addition, they need to have a strong central authority to defend journalists and journalism in wartime, where journalists are regularly threatened, abducted and sometimes killed. Also, the Libyan Journalists Syndicate should stress the importance of the media’s self-regulation to guarantee their rights to freedom of expression, grant their readers’ respect and minimise government’s interference. Finally, they need to develop new laws to grant media freedom from regulations and restrictions, as well as defend and promote democracy, the citizens’ right to be informed, as well as their right to discuss and disseminate information. There is also the need to implement articles in the constitution, articles about the protection of political speech, which would be specific enough to differentiate between what is legally permitted and what may be ethically offensive. Originality/value This study will help the new Libyan parliament after the legislative elections on 24 December 2021 to amend the media laws articles in the constitution.